Behcet's-like syndrome following pembrolizumab: An immune-related adverse event associated with programmed death receptor-1 inhibitor therapy. (June 2020) - Thomas, Steffi; Bae, Chay; Joy-Ann, Tabanor; Traverse, William
Introduction: The landscape for the treatment of metastatic melanoma has been revolutionized with the introduction immune checkpoint inhibitors. Immune checkpoint inhibitors have now become the standard of care for the treatment of cancers. These immune agents including programmed death receptor-1 inhibitors, programmed death-ligand 1 inhibitors and cytotoxic T-lymphocyte antigen-4 inhibitors have shown promising results but have been associated with numerous immune-related complications. Pembrolizumab, a programmed death receptor-1 inhibitor, has been associated with a number of immune-related adverse events affecting multiple organ systems including integument, ocular, endocrine, cardiovascular, pulmonary, renal, gastrointestinal, and musculoskeletal system. Case report: We present a case of an 88-year-old Caucasian male with metastatic melanoma of the face with metastasis to the right fifth cranial nerve and into the right cavernous sinus. He underwent resection of the melanoma and was placed on pembrolizumab at 2 mg/kg every three weeks. Interestingly, 24 months on pembrolizumab therapy, he developed corneal erosions, oral and genital ulcerations. Management and outcome: Patient completed his 24 months of pembrolizumab and was started on prednisone and colchicine with improvement in his symptoms. At his follow-up eight months, he had recurrence of an oral ulcer. Discussion: Here we present a rare case of an elderly male on pembrolizumab who suffered from corneal erosions, oral and genital ulcers, a syndrome similar to Behcet's disease. Given that pembrolizumab and other immune checkpoint inhibitors are being utilized in the treatment of cancers, physicians should be aware of the wide range immune-related adverse events including the possible Behcet's-like syndrome presentation.